Nilai-Nilai Dakwah Dalam Film Surau Dan Silek (Analisis Semiotika Roland Barthes) - Lola Indriani; Khairuddin Khairuddin; Yusuf Afandi; Muhammad Fajri (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
The films Surau and Silek are family films that tell the story of Minangkabau culture which has long been abandoned and has two different perspectives between an 11-year-old elementary school student and a 62-year-old retired lecturer. The film Surau and Silek raises the story of Minangkabau martial arts side by side with the values of da'wah in which the film depicts that if learning martial arts is not based on faith then life will be in vain. Based on the background above, the author formulates a question, namely how are the values of da'wah in the films Surau and Silek. This study used qualitative research methods. The author obtains data from observation activities by watching and observing every scene and dialogue that occurs in the film. The author also separates each scene which contains elements of da'wah values, then the author analyzes it. The theory used in this study is Roland Barthes' semiotic theory by using three meanings in analyzing. The three meanings include denotative, connotative, and mythical meanings. In the films Surau and Silek, scenes that symbolize the values of da'wah are raised, such as the five daily prayers, meditation, tawakal, three uninterrupted practices and amar ma'ruf nahi munkar. The object that appears is like in the scene when Adil is reminded by his mother about three continuous practices, one of which is the prayer of a pious child. And there are also scenes where prayer is more important than other matters.